Misfolded opsin mutants display elevatedβ‐sheet structure. Issue 20 (7th September 2015) - Miller, Lisa M.; Gragg, Megan; Kim, Tae Gyun; Park, Paul S.-H.
Abstract : Mutations in rhodopsin can cause misfolding and aggregation of the receptor, which leads to retinitis pigmentosa, a progressive retinal degenerative disease. The structure adopted by misfolded opsin mutants and the associated cell toxicity is poorly understood. Förster resonance energy transfer (FRET) and Fourier transform infrared (FTIR) microspectroscopy were utilized to probe within cells the structures formed by G188R and P23H opsins, which are misfolding mutants that cause autosomal dominant retinitis pigmentosa. Both mutants formed aggregates in the endoplasmic reticulum and exhibited altered secondary structure with elevated β ‐sheet and reduced α ‐helical content. The newly formed β ‐sheet structure may facilitate the aggregation of misfolded opsin mutants. The effects observed for the mutants were unrelated to retention of opsin molecules in the endoplasmic reticulum itself. Abstract : G188R and P23H opsin mutants are misfolded and cause retinitis pigmentosa. FRET and FTIR were employed to study the structure of misfolded opsin mutants. Misfolded opsin mutants form aggregates in the endoplasmic reticulum. Misfolded opsin mutants display elevated β ‐sheet and reduced α ‐helical content.